The Brazilian National Institute of Meteorology (INMET) and its contributions to agrometeorology (Agrometeoros, 2016)
From its inception in 1909 under the Ministry of Agriculture, INMET has targeted its role as the public provider of weather, climate and related information which may help the agricultural sector to cope with the risks resulting from adverse atmospheric conditions. The Institute’s contributions have evolved from gathering and offering data – initially obtained by means of meteorological gauges only, but nowadays also from satellites – to increasingly more sophisticated products. These include regular weather prediction and alerts; climate monitoring and climatological maps and data; increasingly accurate detailed numerical weather prediction; stochastic and statistical climate forecast models and seasonal forecasts. The Institute also dedicates significant efforts to developing application products, particularly for users of the agricultural sector, individual farmers and cooperatives and policy makers. Sisdagro, a decision support system for agriculture, and LATIS, a laboratory for the application of satellite image information and climate information to crop monitoring, in cooperation with CONAB, are notable examples. INMET intends to strengthen ties with other specialized institutions nationally and internationally, to amplify the range of application products and services directed to the agricultural sector and to enhance its channels of communication with final-users, to improve the usefulness of the products and services offered.
Keywords: meteorological service; agriculture; application products; climate information; climate forecast; decision-support system